Analisis Peran Koperasi Simpan Pinjam Syari’ah dalam Meningkatkan Kesejahteraan Anggota - Subadriyah Subadriyah (Universitas Muhammadiyah Sidoarjo, 2018)
Aim of this research is to examine that crediting by savings and credit cooperatives to debtors, whether the provision has been effective and on target and credit granting has been used wisely by the debtor and not for consumptive purposes. The methodology used is qualitative approach with phenomenological study method. Subjects in this study are recipients of credit (debtor) of savings and loan cooperatives in Jepara and the location of research there are 2 namely: Savings and Loan Cooperative Syari'ah A and Savings and Loan Cooperative Syari'ah B. And from this research found that the granting of credit is considered not effective by sharing reasons